2024
DOI: 10.1186/s12887-024-04540-5
|View full text |Cite
|
Sign up to set email alerts
|

Multivitamin consumption and childhood asthma: a cross-sectional study of the NHANES database

Li Zhang,
Yali Xu,
Xuemei Li
et al.

Abstract: Background Dietary intakes of vitamins are associated with asthma. However, previous studies mainly explored the association between a single vitamin intake and asthma, which did not take the multivitamins into consideration. Herein, this study aims to explore the overall effect of dietary multivitamins consumption on childhood asthma. Methods Data of children and adolescents (aged 2-17 years old) were extracted from the National Health and Nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Eight studies have reported choline intake in adults [ 17 , 18 , 24 , 27 , 28 , 54 , 66 ], one study measured choline intake in children [ 31 ], and four studies have recorded choline intake in pregnant women [ 13 , 33 – 35 ]. Among the twenty-one studies measuring choline intake in non-European countries, the majority (52%) were conducted in the USA [ 19 , 20 , 25 , 32 , 55 – 57 , 62 – 65 ], while the others were carried out in Palestine [ 58 ], South Africa [ 59 ], Australia [ 36 , 60 ], Mexico [ 23 ], Taiwan [ 16 ], Iran [ 22 , 29 ], Canada [ 21 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies have reported choline intake in adults [ 17 , 18 , 24 , 27 , 28 , 54 , 66 ], one study measured choline intake in children [ 31 ], and four studies have recorded choline intake in pregnant women [ 13 , 33 – 35 ]. Among the twenty-one studies measuring choline intake in non-European countries, the majority (52%) were conducted in the USA [ 19 , 20 , 25 , 32 , 55 – 57 , 62 – 65 ], while the others were carried out in Palestine [ 58 ], South Africa [ 59 ], Australia [ 36 , 60 ], Mexico [ 23 ], Taiwan [ 16 ], Iran [ 22 , 29 ], Canada [ 21 , 61 ].…”
Section: Resultsmentioning
confidence: 99%